2012
DOI: 10.1021/ac300305s
|View full text |Cite
|
Sign up to set email alerts
|

Dried Blood Spot Analysis by Digital Microfluidics Coupled to Nanoelectrospray Ionization Mass Spectrometry

Abstract: Dried blood spot (DBS) samples on filter paper are surging in popularity as a sampling and storage vehicle for a wide range of clinical and pharmaceutical applications. For example, a DBS sample is collected from every baby born in the province of Ontario, Canada, for quantification of approximately one hundred analytes that are used to screen for 28 conditions, including succinylacetone (SA), a marker for hepatorenal tyrosinemia. Unfortunately, the conventional methods used to evaluate DBS samples for newborn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
105
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(105 citation statements)
references
References 31 publications
0
105
0
Order By: Relevance
“…This high level of integration enables device architectures capable of executing thousands of predefined "unit cell" reactions in parallel, with applications ranging from protein structure (4) and interaction studies (7,8) to single-cell analysis and genomics (2,9,10). Two-phase flow systems that manipulate picoliter (pL) volume droplets in closed channels have been shown to be ideally suited to high-speed serial analysis for use in high-throughput screening applications (11) and sample preparation for genomics (12), while the programmable manipulation of nanoliter (nL) volume droplets using electrostatic forces has received increasing attention as a potential platform for sample processing automation in proteomics and medical diagnostics (13).…”
mentioning
confidence: 99%
“…This high level of integration enables device architectures capable of executing thousands of predefined "unit cell" reactions in parallel, with applications ranging from protein structure (4) and interaction studies (7,8) to single-cell analysis and genomics (2,9,10). Two-phase flow systems that manipulate picoliter (pL) volume droplets in closed channels have been shown to be ideally suited to high-speed serial analysis for use in high-throughput screening applications (11) and sample preparation for genomics (12), while the programmable manipulation of nanoliter (nL) volume droplets using electrostatic forces has received increasing attention as a potential platform for sample processing automation in proteomics and medical diagnostics (13).…”
mentioning
confidence: 99%
“…There are several studies directed at using an air environment to actuate the liquids by using smaller electrodes and more hydrophobic surfaces. 22 If the contact angle of the droplet on the electrode is large enough in air, then the oil environment can be avoided. Pumping and collecting the droplets are also required for the staining experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Further refinements to the technique, including simplified chip fabrication and improved liquid actuation, have recently been reported that are specifically aligned with optimising DBS direct analysis. This work compared newborn screening of succinylacetone (a marker for hepatorenal tyrosinemia) in DBS samples using a conventional manual extraction technique and DMF and demonstrated no significant difference in the two sets of data (111) . …”
Section: Digital Microfluidics (Dmf)mentioning
confidence: 99%